Undiagnosed diabetes mellitus in tuberculosis: A Lagos report - Ogbera, Anthonia Okeoghene (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Tuberculosis (TB) and diabetes mellitus (DM) are two diseases that are individually relatively common and of immense public health significance globally. There is a growing awareness on a global scale on the possible relationship between TB and DM. Nigeria is a country with a high burden of TB and an increasing incidence of DM. We set out to determine the frequency of occurrence of undiagnosed DM in TB patients. MATERIALS AND METHODS: This was an observational study that was carried out in TB patients recruited from 56 DOT centers in Lagos, Nigeria. The main objective of the study was to determine the disease burden of DM in patients with TB by comparing the frequency of occurrence of DM in TB to the occurrence of DM in people without TB. Screening was carried out by staff-nurses and community health workers-of these DOT facilities who all had capacity building on the detection of DM at the start of the project. RESULTS: Of 4000 TB patients, a total of 480 (12.3%) had DM. Of the pool of DM patients, newly diagnosed cases of DM were 310 (8%) in number and previously known persons with DM were 170 (4.3%). The newly diagnosed cases of DM made up 64% of the cases of DM. In the study population without TB, a total of 112 (5.6%) had DM. The number of newly diagnosed cases of DM were 40 in number and these made up 2% of this study group. The number of persons who were already known to have DM was 72 and these made up 3.6% of the study population. New cases of DM made up 44% of the total number of cases of DM detected in persons without TB. CONCLUSION: The detection rates of DM in patients with TB are higher than in persons without TB. Given the fact that DM may negatively impact TB treatment, we suggest that routine screening be carried out for TB in persons with DM.